Cytological Investigation of Some Selected Elements in the Sputum of Workers in Sokoto Cement Company. - Ibrahim Mohammed * , Habib Nadiya , Imam Malik Kabir , Umar A Kaoje , Abdu Umar , Usman Abubakar , Mohammed Ozovehe Musa , Ahmad Muhammad Tangaza, Rilwan Isah Tsamiya , Okechi Obioma Onyemaechi. (Sokoto Journal of Medical Laboratory Science)
Cement is produced through heating a homogenous blend of limestone and clay, which is adjusted to a content of calcium, silicon, aluminum and iron. Workers in the cement factory are exposed to health hazards of different types such as dust, gases and fume which are responsible for occupational lung diseases. The aim of this study is to investigate some selected elements in the respiratory tract of workers due to inhalation. This comparative cross-sectional study was carried out among 48 Sokoto Cement company workers of all ages who voluntarily participated in this study. Ten non- Sokoto Cement company workers were monitored as controls. Written informed consent and questionnaire for the research was distributed to the subjects to complete. Sputum sample was collected from each subject and smeared onto 9 clean glass slides and fixed immediately in 95% alcohol. The smears were stained by H & E, PPB and Vonkossa staining method. The slides were examined microscopically under X40 objective. Majority of workers are within the age range of 25-29 years (25%), followed by age range of 35-39 years (18.75%), while those with age range 20-24 years had the lowest percentage of 2.08%. Workers were characterized based on years of occupationally exposed to cement dust. Those exposed for 3-9 years of exposure constituted 27.08% of subjects, followed by those exposed for 10-14 years 22.92% and those exposed for 25-29 years constituted 4.17%. Majority of cement workers had normal epithelial lining with sufficient alveolar macrophages, inflammatory cells. Majority of the occupationally exposed cement workers and non-exposed have calcium and iron in their sputum. The cytological result of this study shows that there is no evidence that exposure to cement dust predispose to cancer. Exposure to cement dust is a risk factor for susceptibility to inflammatory changes and the cement workers are inhaling calcium and iron as non-toxic constituents of cement dust.